The Influence Of Increased Income From Mudharabah Profit Sharing On Customers' Interest In Paying Zakat (Case Study Of Bank Sumut Syariah Kcp Marelan Raya) - Hasrimy, Nabila Felicia; Nasution, Yenni Samri Juliati; Jannah, Nurul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Zakat is an important instrument in balancing the economy and reducing poverty levels in society. However, the awareness of some people in paying zakat is still low, especially among Islamic banking customers. In this context, the increase in income from mudharabah contracts in Islamic banks is expected to encourage customers' interest in paying zakat, considering that zakat is an obligation for those who have reached the criteria as muzakki. The purpose of this study is to see how the effect of increasing income on interest in paying zakat. The research method used is descriptive research with a quantitative approach. The sample in this study amounted to 90 respondents and the data were analyzed by Multiple Linear Regression Test. The results of this study indicate a significant influence between income and interest in zakat with a p-value of 0.000 (